New Five Year Plan (1978-83) Sector -Information, Publicity and Tourism Draft Annual Plan 1978-79. Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1978)
The A&N Islands which is a Union Territory remains one of the remotest parts of the Indian Union. the isolation caused by vast stretches of sea has been standing in the way of emotional integration. the people living in the islands and haling from different States on the mainland were drafted for settlement in the islands at different stages of the territory’s onward march. This rightly justify the Territory’s claim for being treated as ’India in Miniature.
Andaman and Nicobar Administration